Plant-derived gum as a gelatin alternative in the formulation of probiotic-enriched toffee candy - Recep Gunes; Didem Sözeri Atik; Ibrahim Palabiyik; Nevzat Konar; Davut Karahan; Reema Tayyem (Applied Food Research)
The conventional toffee type candy production process starts with high heating step and limits the use of functional ingredients and/or low heat stability compounds in the formulation. In this study, an innovative approach was employed to investigate the effects of replacing gelatin in toffee production with a plant gum (kenger gum) obtained from Gundelia tournefortii L. on different probiotic strains' (Lactobacillus casei and Lb. plantarum) viability as well as physicochemical, texture, and sensory properties during the storage period. Accordingly, the moisture contents of kenger gum added sugared (KS), sugar-free (KSF) and control groups were found as 5.59–6.32, 4.29–4.88, and 5.09–5.81 g/100 g, respectively (p < 0.05). The highest glass transition temperature (Tg) values were found in KSF samples and the incorporation of polyols in formulation resulted in the highest hardness values (49.713–128.489 N) in the same samples (p < 0.05). The use of kenger gum in toffee type candy production was effective in the instrumental color properties of the samples, while the difference in the use of probiotic culture did not cause any change. It was determined that kenger gum and polyols had an effect on the sensory parameters of the samples. However, the most notable finding was that there were more probiotic counts in the kenger gum added samples; for instance, the viability results of Lb. casei in KS, KSF and control samples were determined as 5.49, 8.21, 4.57 log CFU/g, while the Lb. plantarum counts were found as 4.39, 7.14, and 4.08 log CFU/g at the end of the 90-day storage period, respectively.